2014
DOI: 10.1038/bjc.2014.628
|View full text |Cite
|
Sign up to set email alerts
|

MRI reveals the in vivo cellular and vascular response to BEZ235 in ovarian cancer xenografts with different PI3-kinase pathway activity

Abstract: Background:The phosphoinositide-3 kinase (PI3K) pathway is an attractive therapeutic target. However, difficulty in predicting therapeutic response limits the clinical implementation of PI3K inhibitors. This study evaluates the utility of clinically relevant magnetic resonance imaging (MRI) biomarkers for noninvasively assessing the in vivo response to the dual PI3K/mTOR inhibitor BEZ235 in two ovarian cancer models with differential PI3K pathway activity.Methods:The PI3K signalling activity of TOV-21G and TOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…21 Only voxels with at least 50% enhancement after 1 min were considered. 21 Only voxels with at least 50% enhancement after 1 min were considered.…”
Section: In Vivo Mri and Data Analysismentioning
confidence: 99%
“…21 Only voxels with at least 50% enhancement after 1 min were considered. 21 Only voxels with at least 50% enhancement after 1 min were considered.…”
Section: In Vivo Mri and Data Analysismentioning
confidence: 99%
“…Inhibition with BEZ has effects on several downstream effectors, including AKT, ribosomal protein S6 (S6), and the translation initiation factor 4E binding protein 1. It has previously been tested for use in hepatocellular carcinoma, multiple myeloma, and other cancers that commonly have mutations or increased gene expression that lead to overactivation of the PI3K pathway (Baumann et al, 2009;McMillin et al, 2009;Kirstein et al, 2013;Cebulla et al, 2015). BEZ has also been shown to have beneficial effects in combination with cytotoxic agents, including DOX (Manara et al, 2010;Schult et al, 2012;Westhoff et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…117,118 Both DW-MRI and DCE-MRI have been proposed as tools for measuring response to PI3K pathway inhibitors and have been evaluated in preclinical in vivo models. [119][120][121] In a recent study, ADC was found to be a useful biomarker for response to the dual PI3K-mTOR inhibitor BEZ235 in an ovarian cancer xenograft model. 119 In the same study, DCE-MRI, which provides information on tumor perfusion and vascular permeability also proved to be a useful biomarker for response.…”
Section: Biomarkers Of Metabolic Effectmentioning
confidence: 99%
“…[119][120][121] In a recent study, ADC was found to be a useful biomarker for response to the dual PI3K-mTOR inhibitor BEZ235 in an ovarian cancer xenograft model. 119 In the same study, DCE-MRI, which provides information on tumor perfusion and vascular permeability also proved to be a useful biomarker for response. The parameter v e is a measure of the extravascular extracellular space and, similar to ADC, may be related to the cellular density of the tumor tissue.…”
Section: Biomarkers Of Metabolic Effectmentioning
confidence: 99%